Resistance switching of BST thin films - Zhuo, Karen Jie Fang. (2011)
The purpose of this project is to study the I-V characteristics of resistance switching oxides to give us a better understanding of their behaviors and the possibility of implementing them into memory devices. This study focuses on barium strontium titanium oxide. The sample is prepared by pulse laser deposition and the properties are studied by taking IV measurements at different holding times, and under different electric fields. These measurements are taken before poling, and after negative and positive poling. The samples are also studied using Scanning Kelvin Probe Microscopy to correlate the IV behaviors with local defects.